The victim's responsibility and its impact on mitigating the perpetrator's punishment - Ibrahim Saad Al-Shoqiran (International Journal of Law Research and Studies, 2025)
This research is founded on elucidating the victim’s responsibility for the crime committed against them. It explores the notion that, in certain offenses, the victim may be the primary cause of the crime or a significant contributor to it. The study examines specific cases where the victim is deemed responsible from the perspective of Islamic jurisprudence. These include: first, repelling an unjust aggressor without rightful cause; second, the aggressor against personal honor; and third, instances where a person provokes another, leading to a crime being committed against them. The research concludes that thoroughly examining the facts and circumstances of a crime, consulting experts, and utilizing modern technology can significantly impact the adjudication of certain criminal cases. Furthermore, in specific instances of crimes, the victim’s actions may render them fully accountable, thereby absolving the perpetrator of responsibility or partially shifting the liability, resulting in a mitigated penalty for the offender.
Keywords: Responsibility; Victim; Perpetrator; Punishment